Maqasid Al-Shari’ah and preservation of basic rights under the theme “Islam and its perspectives on global & local contemporary challenges” - Afridi, Muhammad Adil Khan (Journal of Education and Social Science (JESOC), 2016)
Now more than ever, there is a necessity to clarify the Shari’ah of Islam. Daily, the media, government institutions, and lobbying groups depict Islam as a religion bent on domination with the goal of enforcing the Shari’ah on Muslims and non-Muslims alike. Unfortunately, a small minority of Muslims promoting a deviant, archaic legal system far removed from the principles and purposes (Maqasid) of the spirit of Islam are complicit in perpetuating this biased narrative. We are living in a time when the religion of Islam is being maligned by outside and inside forces. The Shari’ah of today needs to be clarified as a continuation of Shari’ah. The methodology of Maqasid al-Shari’ah needs to be articulated and promoted to the Muslim and the non-Muslim alike. When the Shari’ah of Islam can be realised and clarified through universal principles and purposes (Maqasid), the Muslim community (Ummah) can rectify Islam from those who have corrupted the tradition from within. The Ummah of the Prophet (p.b.u.h) needs to be awakened from its slumber and turn to the higher Fiqh (Maqasid al-Shari’ah) to renew (Tajdid) and infuse the spirit of Islam into the hearts and minds of the believers. This study discusses the Maqasid al-Shari’ah, its history and background, the famous three categories of Maqasid al-Shari’ah and its preservation of five basic rights. Today the world wants to know the relationship between the human rights and Shari’ah. This paper is a step in that direction based on a framework of analyses that exemplifies the spirit of Islamic law in its treatment and guidance of mankind.